Formulasi Strategi : Usaha Kerajinan Kulit - Adrianus Aprilius (Musamus Journal of Business & Management, 2020)
This research is designed to compile and try out appropriate strategy formulations to be applied to the gold crocodile skin craft business. The research method used is qualitative and quantitative methods. The results showed that the SWOT matrix analysis results obtained six alternative strategies, namely: (1) taking various exhibitions in the city or outside the city, (2) Promotion through social media, (3) Obtained from a network of raw material providers, (4) make your own crocodile breeding, (5) offer cooperation with local governments, (6) attend seminars or training which is held as a means of promotion. Based on QSPM analysis, alternative strategies that are appropriate and can be carried out by the business of kullit crocodile skin crafts are (1) Following various exhibitions in the city or outside the city (STAS: 9,20), (2) Promotion through Social Media (STAS: 7,15), (3) Making Own Crocodile Breeding (5,32), (4) Expansion of Collaboration Network of Raw Material Providers (STAS: 5.14), (5) Taking seminars with the help of training which is held as a promotional tool ( STAS: 5,06) (6) Cooperation visit with local government (STAS: 4,48) Keywords : Formulasi Strategi, SWOT,QSPM